Sexual and Reproductive Health Experiences of International Students Studying in Universities of Western Countries: A Critical Literature Review - Kwame, Abukari; Li, Hua; Petrucka, Pammla; Maina, Geoffrey (Journal of International Students, 2023)
Engaging in sexual relationships is part of adulthood, but doing so in a foreign country can be risky because unsafe sexual experiences can have severe consequences for international students. This review explored sexual and reproductive health (SRH) experiences and needs of international university students in Western countries to identify challenges and gaps and to discuss critical SRH interventions. Four databases (Scopus, Embase, Web of Science, and PubMed) were searched for peer-reviewed journal articles published between 2000 and 2023. After screening 1607 articles, 10 met the inclusion criteria. Results of the review showed that many international students lack comprehensive knowledge about sexual health and sexually transmitted infections. They often obtain SRH information from informal sources, face language barriers, and experience difficulties navigating the healthcare systems of their host countries. University sexual wellness programs should examine how cultural orientations impact the sexual health of international students and provide culturally appropriate SRH interventions.